EFFECTS OF MOTHER’S LITERACY ON CHILD HEALTH ASSESSED BY PERSONAL HYGIENE, NUTRITIONAL AND VACCINATION STATUS - Zeb, Junaid; Zeeshan, Muhammad; Kamal, Muhammad; Saleem, Maaz; Shah, M. Tariq (Pakistan Journal of Physiology, 2017)
Background: In Pakistan, literacy means ‘the ability to read and write’. Mother’s education is a stronger determinant of child survivorship. This study was carried out in order to determine the impact of mother’s literacy on child health in terms of personal hygiene of child, nutritional status and vaccination status, and to compare the child health status of literate and non-literate mothers. Methods: It was a cross-sectional study carried out in Paediatric Unit, Ayub Teaching Hospital, Abbottabad, from Dec 2015 to Aug 2016. Data was collected using non probability sampling and analysed on SPSS-21. Frequencies and percentages were calculated for categorical variables like gender, residence, education, immunization and hygiene status, and Mean±SD were calculated for quantitative variables like age. Results: Among total 160 children, mothers of 48 (30%) children were completely uneducated. Nutrition status showed that 89 (55.6%) were of normal height for age while rest of them were having stunting of mild to severe categories. Immunization of 135 (84.4%) of the children was done as per their age. Regarding hygiene, clothing of 129 (80.6%) was clean, nails of 95 (59.4%) children were properly clean and trimmed, while hair hygiene of 119 (74.4%) children and dental hygiene of 109 (68.12%) children was well maintained. Majority of those whose immunization, nutrition, and hygiene status was maintained had educated mothers. Conclusion: Maternal literacy has a direct effect on the overall child health with respect to personal hygiene, nutritional and vaccination status. Pak J Physiol 2017;13(1):22–5